(untitled) (Research, Society and Development, 2020)
Coronavirus is a family of viruses that cause respiratory infections. COVID-19 is a disease caused by the SARS-CoV-2 coronavirus, which presents a clinical picture ranging from asymptomatic infections to severe respiratory conditions. Due to the spread of the disease across continents, the current situation is characterized as a pandemic. In view of this scenario, there was an awakening to discuss: The possibilities of occupational nursing assistance to health professionals in front of the new coronavirus. The current work is an integrative bibliographic research, with a qualitative approach, descriptive, exploratory and documentary analysis. Fifteen documents were collected, however only 06 achieved the objectives. Among the analyzes, the insufficient demand for individual and collective protective equipment was highlighted, as well as the lack of training for health professionals regarding the conduct they should adopt in the face of the new virus pandemic and concluding that nursing work has the role of taking care of the well-being of employees and the company.